Potentiality of virtual trails as a pedagogical activity that triggers aesthetic-environmental reflection - Andrade, Danielle Müller de; Montiel, Fabiana Celente; Silva, Patrícia da Rosa Louzada da (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
This paper aims at introducing the potentiality of the use of virtual trails as an innovative and sensitizing pedagogical activity that triggers aesthetic-environmental reflection in Basic and Higher Education. One hundred and seven students that attend the Instituto Federal Sul-rio-grandense (IFSul) in Pelotas, Rio Grande do Sul (RS) state, Brazil, and the Universidade Federal do Rio Grande (FURG), in Rio Grande, RS, Brazil, participated in the study. After carrying out the pedagogical activity which consisted in following three virtual trails, they filled out an online form about the use of virtual trails as pedagogical activities to discuss socioenvironmental issues. The corpus was analyzed by the Thematic Analysis which led to two categories of analysis: a) Virtual trails as a strategy for encouraging aesthetic-environmental reflection; and b) Connection with nature. Results showed an innovative pedagogical activity that enables contact with the natural environment, encourages aesthetic-environmental reflection and develops human sensitivity, creativity and criticality by means of whole Education.